Asset Booms and Structural Fiscal Positions : The Case of Ireland - Kanda, Daniel (IMF Working Papers; Working Paper, 2010)
Asset booms and sectoral changes can distort traditional estimates of structural fiscal revenue, and could lead to serious fiscal policy errors. This paper extends the estimation of structural revenues to take account of asset prices and sectoral changes, and applies this to the case of Ireland, where a property bust has revealed a large hole in the public finances. It is shown that excluding these factors led to a substantial bias in the estimation of structural revenues, and the structural balance prior to the crisis was much larger than earlier estimated.